Protected wading bird species threaten relict centenarian cork oaks in a Mediterranean Biosphere Reserve: A conservation management conflict - García, Luis V.; Ramo, Cristina; Aponte, Cristina; Moreno, Adela; Domínguez, María T.; Gómez-Aparicio, LORENA; Redondo, Ramón; Marañón, Teodoro (Biological Conservation, 2011)
Conservation management conﬂicts frequently arise when an overpopulation of a protected organism has negative effects on other valuable elements in the same ecosystem. We studied the interactions between a colony of protected tree-nesting wading birds and a remnant population of centenarian cork oaks that was part of the formerly dominant forests in the Doñana Biological Reserve (SW Spain). A signiﬁcant increase in the tree mortality rates has been recorded in areas that are yearly inﬂuenced by the bird colony. We analysed a cohort of surviving trees using a gradient of nesting bird inﬂuence. Tree-nesting history, bird isotopic signature (d 15 N), tree health-related parameters (defoliation, d 13 C and leaf surface coverage by faeces) and several soil variables were evaluated. Bird inﬂuence was related to increased soil salinity. This increase correlated to increased water-use efﬁciency for the leaves and to crown defoliation, suggesting that the heavily occupied trees are under higher stress and in poorer health condition than the unoccupied ones. We tested structural equations models (SEM) that were based on hypothesised bird effects on the health of the trees. Soil-mediated effects of the nesting birds best explained the symptoms of the declining health of the trees, whereas the percent of leaves’ surface that was covered by faeces did not improve the ﬁtted SEM model. For the reserve’s managers, a challenging trade-off exists between preserving the relict trees, which have a high genetic diversity and a key ecological role in these savannah-like ecosystems, and maintaining the current nesting area for these protected, but expanding, wading birds.
Keywords: Colonial waterbirds; d13C; d15N; Doñana; Heronry; Indirect effects; Quercus suber; Stable isotopes